A Journey of Process Safety Management Program for Process Industry - Hanida, Abdul Aziz; Azmi, Mohd Shariff (Penerbit Universiti Malaysia Pahang, 2017)
The growth of process industries and global economies are dependent on technology advances and innovations. However, the effects of these advancements often lead to more complex processes and comparatively severe operating conditions such as high pressure, temperature and reactive chemical with exotic chemistry. With the rapidly increasing scale and complexity of the process, it is becoming harder to control accidents in process plants. In most of the past situations, it appears that accidents could not be controlled solely by engineering practices and traditional occupational safety but should be immersed with safety management programs specifically Process Safety Management (PSM) to enhance the effectiveness of technical solutions. This paper addressed PSM program as stipulated by OSHA 29 CFR 1910.119. The PSM standard was implemented following a number of disasters, including accidents in Bhopal, India (1984) and Pasadena, Texas (1989). In Malaysia, Control of Industrial Major Accident Hazards (CIMAH) 1996 Regulation which has the requirements attribute to PSM standard also discussed.